Effectiveness And Acceptability Of Audio Amplifier Trainer - Donn Raymond Labalan Bermundo (Universitas Ahmad Dahlan, 2022)
Audio amplifier servicing is one of the competencies to acquire electronic product assembly and servicing skills. The students taking this course found difficulties in learning the basic troubleshooting of an audio amplifier because of the absence of available learning materials for the hands-on experience in understanding essential audio amplifier servicing. It inspired the researcher to develop the audio amplifier trainer through research and development to improve the knowledge and skills of electronic product assembly and servicing students through simulation of the basic troubleshooting and servicing of a transistorized audio amplifier circuit. The study used the exploratory sequential approach method to determine the level of instructional device's level of acceptability and effectiveness; data were statistically analyzed using the weighted mean and the t-test; according to the study's findings, the experts assess portability, usability and content assessment of the instructional device asVery Much Acceptable. The trainer effectively demonstratedthe basic primary rubles of an audio amplifier, revealing the significant difference in the level of performance between the controlled and experimental groups, showing that the trainer is an effective instructional device.